Changes in laryngeal motoneurone activity and in laryngeal calibre during the expiration reflex - Stránsky, A; Tomori, Z (Physiologia Bohemoslovaca, 1979)
In anaesthetized and paralysed cats, the response of the laryngeal motoneurones during the expiration reflex is characterized by pronounced activation of the expiratory laryngeal motoneurones in the compressive phase and the subsequent constriction phase. In the expulsive phase the frequency of these discharges is significantly reduced. The inspiratory laryngeal motoneurones are inhibited during the reflex. The expiration reflex, in anaesthetized cats, is accompanied in the compressive phase and the subsequent constriction phase by a two-phase increase in laryngeal resistance. In the expulsive phase there is a significant drop in resistance.
Keywords: Electrophysiology; motorické neurony; Cats; akční potenciály; Motor Neurons; Action Potentials; Larynx; Laryngeal Nerves; mužské pohlaví; rezistence dýchacích cest; elektrofyziologie; laryngální nervy; tlak; Pressure; Recurrent Laryngeal Nerve; dechový objem; Tidal Volume; kočky; ženské pohlaví; zvířata; larynx; nervus laryngeus recurrens; Airway Resistance; Female; dýchání; Male; Respiration; Animals